The Occurrence of Metabolic Syndrome in Women of Childbearing Age Frequency - Yahyоeva Hilola Sharifovna (American Journal of Biology and Natural Sciences, 2024)
Metabolic syndrome is a set of pathological processes in the form of insulin resistance, abdominal obesity, dyslipidemia, and arterial hypertension, and which is linked to an increased risk of cardiovascular disease, diabetes, nonalcoholic liver disease, and chronic kidney disease. The presence of each component of the metabolic syndrome increases the risk of cardiovascular disease and the presence of several components in one patient increases this risk even more.